A Descriptive Study on the Implementation of SAMR Model in English Language Teaching of Eleventh Grade Students in Banyuwangi Senior High Schools - Efina Ekawati; Tri Mulyati; Abdul Halim (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2020)
This is descriptive qualitative research design. The respondent of the research were taken by using purposive sampling. The respondent were three English teachers in SMAN 1 Banyuwangi, SMAN 1 Giri and SMAN 1 Glagah. The data were taken by using documentation, interview and questionnaire. The researcher analyzed the data of questionnaire by using Likert scale. The result of the data analysis was determined based on the SAMR model. Based on the data analyzed by using Likert scale, the English teachers in Banyuwangi high schools often implemented SAMR in English language teaching and the index percentage was 60%. The percentage of substitution level was 67%, as a result the respondents often used technology in substitution level. The percentage of augmentation was 62%, so the English teacher in Banyuwangi high schools often implemented technology in augmentation level. In Modification level, the percentage was 62%, it means the English teachers in Banyuwangi senior high schools often used technology in modification level. The percentage of the redefinition was 50%, as a result, the English teachers of Banyuwangi high schools seldom implemented technology in redefinition level. The English teachers used technology to design the material, so students can understand the material easily. The technology mostly used was LCD and laptop as the tools, also power point and video as the media. the problem that was faced by the respondents was the weakness of WIFI signal. The teachers often used technology in substitution level, augmentation level, and modification level. Yet, the teachers seldom used technology in redefinition level. So, the English teachers are suggested to redesign the material creatively and attractively by using varied application in order to make students more creative and used internet for education by using varied application.